Analisis Investasi dalam Pengembangan Usaha Home Industri Abon Ikan Patin Desa Teluk Ketapang - Endang Meiliani; Afriantoni Afriantoni; Eva Setia Rini (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
The purpose of this study was to determine a business feasibility study on shredded catfish in Teluk Ketapang Village, which was reviewed from the market and marketing aspects, financial aspects, management aspects and economic aspects. The method used is descriptive qualitative method, the method used in data collection is by library, field, observation, interview. Based on the results of research from the marketing aspect as well as the technical and technological aspects of the home industry of catfish floss, Teluk Ketapang Village is feasible to be developed in the Jambi Province, precisely in the Telanai Pura sub-district, Danau Sipin Village. Meanwhile, from the management aspect, it has been prepared and calculated from the budgeted investment such as determining sales every month and year.